GE_GERICHTE C/26437/2010 vom 24. Januar 2014 - GE Cour de justice (2014)
LÉGITIMATION ACTIVE ET PASSIVE; INTERPRÉTATION(SENS GÉNÉRAL); RÉVOCATION(EN GÉNÉRAL); MANDAT; DOMMAGES-INTÉRÊTS; HONORAIRES | CO.404.1; CO.404.2; SIA.102 (2003);